If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2t + -1) + 2t = 6 + -1t Reorder the terms: 3(-1 + 2t) + 2t = 6 + -1t (-1 * 3 + 2t * 3) + 2t = 6 + -1t (-3 + 6t) + 2t = 6 + -1t Combine like terms: 6t + 2t = 8t -3 + 8t = 6 + -1t Solving -3 + 8t = 6 + -1t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add 't' to each side of the equation. -3 + 8t + t = 6 + -1t + t Combine like terms: 8t + t = 9t -3 + 9t = 6 + -1t + t Combine like terms: -1t + t = 0 -3 + 9t = 6 + 0 -3 + 9t = 6 Add '3' to each side of the equation. -3 + 3 + 9t = 6 + 3 Combine like terms: -3 + 3 = 0 0 + 9t = 6 + 3 9t = 6 + 3 Combine like terms: 6 + 3 = 9 9t = 9 Divide each side by '9'. t = 1 Simplifying t = 1
| 6(5m+3)=3(3m+5) | | fu*7+76=12y+9087 | | p-3=114 | | 5x-2-(-3x+4)= | | 6r-9=7+4r | | 5x+7-3(2x+9)=2(x-8)-13 | | 2m+1*5= | | 4(2x+4)-20=12 | | 2(a-8)=10 | | r-ll/3=-7 | | -3(5t-4)+5t=7t-7 | | 2w+4-(3w+6)= | | -75=3g | | 20=-5/3z | | 3p*1/3=114 | | (u-10)*6=48 | | 3*1/3p=114 | | x*log(x)=600000000 | | -2.4n-3+(7.8n+2)= | | Y=-1/2x-12 | | -.5(8x-6)=6x-7 | | 10+6+3x=7*3.5 | | -2m(1+4m)5=-13 | | 2(2l-3+l)=36 | | -(3/x)=0 | | 13/6-1/2 | | 10+4+3x=7*3.5 | | 24.5=2.5-4c | | 7+7y=12x-56 | | -(3/x)0 | | 7v^2+224=-84v | | 10x+20y=360 |